2018
DOI: 10.1128/aac.00873-18
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of Colistin-Containing Combinations against Colistin-Resistant Enterobacteriaceae

Abstract: Resistance to colistin, a polypeptide drug used as an agent of last resort for the treatment of infections caused by multidrug-resistant (MDR) and extensively drug-resistant (XDR) Gram-negative bacteria, including carbapenem-resistant (CRE), severely limits treatment options and may even transform an XDR organism into one that is pan-resistant. We investigated the synergistic activity of colistin in combination with 19 antibiotics against a collection of 20 colistin-resistant isolates, 15 of which were also CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
82
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 54 publications
14
82
2
Order By: Relevance
“…In the present study, the agreement between the TK assay and the DA method was higher among colistin-resistant A. baumannii isolates when colistin was combined with meropenem or Fosfomycin similar to other studies [7,[9][10][11][12][13][14]. The synergistic effect of fosfomycin with carbapenem could be explained by the resistance profile of the strains evaluated-most A. baumannii isolates carried carbapenemase genes (bla OXA-23, bla OXA-143 , and fosA), which confer resistance to fosfomycin.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study, the agreement between the TK assay and the DA method was higher among colistin-resistant A. baumannii isolates when colistin was combined with meropenem or Fosfomycin similar to other studies [7,[9][10][11][12][13][14]. The synergistic effect of fosfomycin with carbapenem could be explained by the resistance profile of the strains evaluated-most A. baumannii isolates carried carbapenemase genes (bla OXA-23, bla OXA-143 , and fosA), which confer resistance to fosfomycin.…”
Section: Discussionsupporting
confidence: 86%
“…The treatment of infections caused by these microorganisms based on identification of resistance mechanisms and drug combinations is usually more effective than empirical treatment [1,4]. Synergy testing can also correlate to a particular resistance mechanism [8,14]. Such correlations might help predict the synergism for a particular antimicrobial combination for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MacNair et al showed that colistin is notably synergistic in vitro with rifampin, the macrolide antibiotic clarithromycin, minocycline, and novobiocin against mcr https://doi.org/10.1016/j.peptides.2018.12.006 Received 31 October 2018; Received in revised form 20 December 2018; Accepted 21 December 2018 strains [13]. Brennan-Krohn et al described the synergism of colistin with rifampin, the macrolide antibiotic azithromycin, minocycline, fusidic acid, linezolid, and several other drugs against mcr and other PMR strains [14]. A plausible explanation for the synergism is that even though the PMR strains can grow at higher concentrations of polymyxins than the polymyxin-susceptible wild-type strains, subinhibitory concentrations of polymyxins are still able to damage the outermost permeability barrier, the outer membrane (OM) of the PMR bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…A plausible explanation for the synergism is that even though the PMR strains can grow at higher concentrations of polymyxins than the polymyxin-susceptible wild-type strains, subinhibitory concentrations of polymyxins are still able to damage the outermost permeability barrier, the outer membrane (OM) of the PMR bacteria. Consequently, the damaged OM allows the entry of drugs normally excluded or partially excluded by the intact enterobacterial OM [13,14] NAB739 is a novel polymyxin derivative [15,16]. It carries only three positive groups, all in strategic positions, instead of five in PMB and colistin (Table 1).…”
Section: Introductionmentioning
confidence: 99%